Comprehensive Analysis of Codon Usage Patterns in Chinese Porcine Circoviruses Based on Their Major Protein-Coding Sequences - Hua Feng; Joaquim Segalés; Fangyu Wang; Qianyue Jin; Aiping Wang; Gaiping Zhang; Giovanni Franzo (Viruses, 2022)
Porcine circoviruses (PCVs) are distributed in swine herds worldwide and represent a threat to the health of domestic pigs and the profits of the swine industry. Currently, four PCV species, including PCV-1, PCV-2, PCV-3 and PCV-4, have been identified in China. Considering the ubiquitous characteristic of PCVs, the new emerged PCV-4 and the large scale of swine breeding in China, an overall analysis on codon usage bias for Chinese PCV sequences was performed by using the major proteins coding sequences (ORF1 and ORF2) to better understand the relationship of these viruses with their host. The data from genome nucleotide frequency composition and relative synonymous codon usage (RSCU) analysis revealed an overrepresentation of AT pair and the existence of a certain codon usage bias in all PCVs. However, the values of an effective number of codons (ENC) revealed that the bias was of low magnitude. Principal component analysis, ENC-plot, parity rule two analysis and correlation analysis suggested that natural selection and mutation pressure were both involved in the shaping of the codon usage patterns of PCVs. However, a neutrality plot revealed a stronger effect of natural selection than mutation pressure on codon usage patterns. Good host adaptation was also shown by the codon adaptation index analysis for all these viruses. Interestingly, obtained data suggest that PCV-4 might be more adapted to its host compared to other PCVs. The present study obtained insights into the codon usage pattern of PCVs based on ORF1 and ORF2, which further helps the understanding the molecular evolution of these swine viruses.